Urban planning by Alejandro de la Sota in the Spanish colonisation: La Bazana - Rubén Cabecera Soriano (VLC Arquitectura)
The Spanish civil war caused the emerging development of the urban theory to come to a standstill, especially in the rural areas which had began to appear at the end of the XIX century, mainly in Europe and the United states. The need to urgently develop a process of interior colonisation in the most disadvantaged areas was solved in favour of the theories of concentration supported by José Tamés facing the colonist disintegration defended by Víctor D’Ors. The system disguised by Tamés –head of the Service of Architecture of the National Institution of Colonisation (NIC)– created population centres distributed throughout the territories colonised by the NIC, whose projects were developed by a large number of architects that formed a genuine architectural and urban laboratory.